GUANGZHOU – TANAH SUCI ISLAM TIMUR JAUH - Cai Jinchen (Humaniora, 2007)
Guangzhou is one of the three most important cities in China with a long history and tradition. This city is a centre of trade and is known as the city of culture. It was one of the places where Islam for the first time spread from Arab to China. One of the evidences of the early spread of Islam to China is the existence of Huaisheng mosque of which it is predicted that the tower was built in the year of 1350 AD. The cemetery of Abu Waqqash who spread Islam to China in the seventh century can also be found in the hill of Guihua in Guangzhou. The people from far away countries such as Arab and Persia admired him and when they arrived in Guangzhou after traveling by sea covering the distance of thousands of kilometers they were proud to be able to pray in front of his tomb.